Features of the Formation and Growth Films Based of PbTe on Mica - Bylina , I.S. (Physics and Chemistry of Solid State, 2015)
The results of comprehensive research vapor-phase condensate on based of PbTe, deposited on mica substrates method of the open evaporation in a vacuum. The analysis of AFM-images constructed histogram distribution of nanostructures on the surface of the film at normal (h) and lateral (D) size. The dependence of the average sizes of nanocrystals in normal (hm) and lateral (Dm) to the substrate surface direction of deposition time τ. Confirmed root dependence medium size of the duration deposition. The analysed feature changes of the form factor of objects on the surface from technological parameters.